Health for all in India: A vision made possible through integrated Public Health and Community Medicine - Manisha Nitin Gore; Sneha Deepak Mallya (Clinical Epidemiology and Global Health)
Background: The outcome cerebral malaria involves an interplay of factors including clinical and biochemical parameters, a deep knowledge of these laboratory biochemical parameters is essential. This study aimed to assess the pattern of the biochemical parameters in children with cerebral malaria and how it may affect the clinical outcomes. Methods: A prospective observational study among fifty subjects at the children's emergency unit of LAUTECH Teaching Hospital, Ogbomoso. The subjects were admitted with a history of fever and altered sensorium, demonstrable malaria parasite in the blood film, and cerebrospinal fluid (CSF) analysis to rule out other central nervous system infections. Samples were collected for malaria parasite, serum electrolytes, urea, creatinine, and blood glucose estimation. The data obtained were analyzed using SPSS version 22. Results: Children with hypoglycaemia had a 3.5-fold relative risk of poor outcome and this is statistically significant. Hyperkalaemia was significantly associated with poor outcomes (RR = 2.57, p = 0.009). Subjects with hypochloraemia had three times the risk of mortality and neurological sequelae with statistically significant association (RR = 3.07, χ2 = 8.519, p = 0.004). There was a significant association between metabolic acidosis and poor clinical outcome. (RR = 1.99, χ2 = 4.089, p = 0.043). The parasite density was significantly associated with the serum bicarbonate (HCO3−) and Chloride, p-value <0.05. Conclusion: Hypoglycaemia, hyperkalemia, hypochloremia and metabolic acidosis were significantly associated with poor outcomes, thus, good predictors of clinical outcomes. Periodic evaluation and monitoring of these parameters is essential for prompt intervention to forestall devastating outcomes.